Explainable Artificial Intelligence for Human–AI Collaboration: Evaluating Trust, Transparency, and Decision-Making Effectiveness in AI-Based Systems - Varsha Negi, Sunil Kumar (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Explainable Artificial Intelligence (XAI) has emerged as a pivotal discipline in bridging the growinggap between complex machine learning systems and human understanding. As AI-based decision-support systems are increasingly deployed in high-stakes domains